2004
DOI: 10.4296/cwrj159
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of Fate and Transport of Metolachlor in a Soil Column Study

Abstract: PRZM2 is a computer model developed to simulate pesticide transport through the soil profile under saturated and unsaturated conditions. The ability of PRZM2 to simulate the fate and transport of metolachlor will be examined and the simulation results from a soil column study will be evaluated. The input parameters and the measured data were obtained from a soil column study. The model outputs were compared to the measured values and statistical analyses were performed using the coefficient of performance appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A limited number of studies have examined metolachlor attenuation in the unsaturated zone. Studies have examined data derived from laboratory experiments (Jebellie et al, 2004; Sanyal and Kulshrestha, 2003; Wietersen et al, 1993) and field sampling efforts (Zacharias et al, 1999; Hippe and Hall, 1996; Smith and Parrish, 1993; Trevisan et al, 1993; Mullaney et al, 1991). Results of these studies have shown that metolachlor concentrations generally taper off to values less than the method reporting limit between 0.1 and 0.5 m and are immeasurable in the saturated zone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies have examined metolachlor attenuation in the unsaturated zone. Studies have examined data derived from laboratory experiments (Jebellie et al, 2004; Sanyal and Kulshrestha, 2003; Wietersen et al, 1993) and field sampling efforts (Zacharias et al, 1999; Hippe and Hall, 1996; Smith and Parrish, 1993; Trevisan et al, 1993; Mullaney et al, 1991). Results of these studies have shown that metolachlor concentrations generally taper off to values less than the method reporting limit between 0.1 and 0.5 m and are immeasurable in the saturated zone.…”
mentioning
confidence: 99%
“…Results of these studies have shown that metolachlor concentrations generally taper off to values less than the method reporting limit between 0.1 and 0.5 m and are immeasurable in the saturated zone. Numerical models, including AgriFlux (Novak et al, 2003), GLEAMS (Zacharias et al, 1999), LEACHM (Trevisan et al, 1993), PRZM (Trevisan et al, 1993), PRZM2 (Jebellie et al, 2004), MACRO (Balderacchi et al, 2002), and Opus (Zacharias et al, 1999), have been used in conjunction with field and laboratory data to examine the capabilities of models to simulate metolachlor leaching and to identify factors affecting attenuation. Most models have demonstrated the capability to simulate metolachlor concentrations near the surface but have been less accurate at forecasting distributions below the root zone.…”
mentioning
confidence: 99%
“…Several hygiene related deaths globally (Victor, 2008). There is researchers, in the area of groundwater/subsurface now an urgent need to scientifically harness both contaminant engineering, have studied contaminant human and material resources especially in the transport and transformation in 1-D laboratory soil emerging field of geoenvironmental engineering in column (Jebellie et al, 2004; Adams and Guzman order to meet the target 10 (Halve, by 2015, the Mirbagheri and Hashemi Monfared, 2009). proportion of people without sustainable access to safe Sand tank model is a 3-D physical aquifer model and drinking water and basic sanitation) of the pertinent ever since, early 1980s, it has been widely employed in millennium development goal (goal 7 -ensure several fields of study in the laboratory to observe environmental sustainability).…”
Section: Introductionmentioning
confidence: 99%